1986
DOI: 10.1038/321177a0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation—a role for a 40K anti-phospholipase A2 protein indistinguishable from lipocortin

Abstract: Stimulus-response (S-R) coupling in platelets requires an intermediary other than an elevation in cytosolic free calcium ([Ca2+]i). While an increase in [Ca2+]i is essential in S-R coupling, effecting phosphorylation of myosin of relative molecular mass (Mr) 20,000 (20 K), platelet activation is also associated with phosphorylation of a 40K protein, which can occur in the absence of changes in [Ca2+]i. The 40K protein is the substrate for protein kinase C (PKC). Mounting evidence suggests that activation of PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…This is probably not the case for 67R, which was revealed as a poor substrate for protein kinase C. As recently shown by Touqui et al [33], platelets contain, in addition to LC, a protein eluting at around 67 kDa upon molecular sieving on a TSK-G2000 column, whose activity is not modulated by protein kinase C activation. It is thus tempting to suggest some similarity if not identity between that platelet protein and the 67R protein from lung.…”
Section: Resultsmentioning
confidence: 62%
“…This is probably not the case for 67R, which was revealed as a poor substrate for protein kinase C. As recently shown by Touqui et al [33], platelets contain, in addition to LC, a protein eluting at around 67 kDa upon molecular sieving on a TSK-G2000 column, whose activity is not modulated by protein kinase C activation. It is thus tempting to suggest some similarity if not identity between that platelet protein and the 67R protein from lung.…”
Section: Resultsmentioning
confidence: 62%
“…Several reports have shown that the 35 kDa and 67-70 kDa lipocortin-like protein are closely related with respect to sequence, antiserum cross-reactivity and binding of Ca 2+ and phospholipid (see [35] for refs). Lipocortin I is a substrate for both the EGF receptor tyrosyl kinase [36] and the protein kinase C (PKC) [2,37]. Antonicelli et al [32] recently showed that among four proteins (32, 35, 36 and 67-70 kDa) of the lipocortin family, only lipocortin I was the endogenous substrate for the PKC in thyroid-stimulating hormone (TSH) treated cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies [36] have postulated a stimulatory role for C kinase in agonist-induced arachldonate release achieved via phosphorylation of the anti-phospholipase A2 protein, lipocortin, with no mention of the type of agonist this would be applicable to. Our results suggest that where the coupling processes involved in arachidonate release are inhibited by C kinase activation, as seems to be the case with thrombin, this inhibition may supercede any stimulatory effects of phosphorylated lipocortin on arachidonate release.…”
Section: Discussionmentioning
confidence: 99%